2023
DOI: 10.1007/s42250-023-00626-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical-Based Evidence of the Health Benefits of Bidens Pilosa Extracts and Cytotoxicity

Abstract: Purpose Bidens pilosa L. is traditionally used as a flavouring agent in foods, in the treatment of diseases, in agriculture as a biopesticide and herbicide, and in the phytoremediation of soils contaminated with heavy metals. The vast range of uses of B. pilosa for a variety of purposes is questionable, hence motivating the objectives of this study, which are to assess the cytotoxicity, health benefits, and/or risks of B. pilosa using chemical-based evidence. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
1
1
Order By: Relevance
“…Various studies have reported these concentration ranges, often falling between 500 µg/ml and over 1,000 µg/ml against various microorganisms. The present results do not categorize these compounds as definitively "good" or "not good, " but they do confirm the low or absent cytotoxic effects compared to other plant extracts [29].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Various studies have reported these concentration ranges, often falling between 500 µg/ml and over 1,000 µg/ml against various microorganisms. The present results do not categorize these compounds as definitively "good" or "not good, " but they do confirm the low or absent cytotoxic effects compared to other plant extracts [29].…”
Section: Discussioncontrasting
confidence: 94%
“…Regarding the toxicity assessments using Artemia salina and the Vero cell line, the CC 50 results exceeded 1,000 μg/ml for both the Bp-mOH extract and the 3 evaluated fractions (BPFC1CL1, BPFC2AE1, and BPFC3MOH1). These results indicated that the extract and fractions were non-toxic [ 29 ]. Such toxicity studies are paramount, providing comprehensive insights into potential non-harmful effects on different organisms and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identifed polyphenols, phenolic acids were notably abundant in the B. pilosa extract. Tese observations are similar to fndings by Idris et al [47], who reported a high prevalence of phenolic acids and their derivatives in B. pilosa extracts obtained through water and 70% ethanolic extraction methods. Te medicinal uses of B. pilosa in traditional medicine and food preservation could be attributed to this high phenolic acid content [21].…”
Section: Polyphenol Groups Identifed In Bidens Pilosa Extract Andsupporting
confidence: 90%
“…A double layer of gauze was used to filter the infusion. A rotary evaporator was used to evaporate the filtrates at 40 degrees Celsius in a vacuum (12,13) . The chemical analysis of dried powdered B. pilosa leaves included the determination of moisture content, total protein, fat, fiber, and ash using the procedures specified in A.O.A.C, (14) , and the determination of carbohydrates content using the method of difference.…”
Section: Methodsmentioning
confidence: 99%